Cost-effective and label-free split aptamer constructs for rapid and visual detection of PDGF-BB protein - Yingping Luo; Tongtong Lai; Yi Tang; Linhui Xie; Jingyan Zhang; Peiyao Chen; Jiancai Tang; Qiang Su; Qiao Liu (Sensors and Actuators Reports)
Though considerable efforts are focusing on the development of different types of sensors for platelet-derived growth factor BB (PDGF-BB) determination, few of these approaches can achieve cost-effective, rapid, and sensitive detecting PDGF-BB by naked eye. Herein, we developed a novel, cost-effective, label-free and robust sensor based on split aptamer recognition and proximity-induced formation of G-quadruplex DNAzyme for rapid and visual detection of PDGF-BB. The two segments of constructed sensor, termed as split aptazyme (SA), were separated in the absence of PDGF-BB, but effectively assemble after binding the target to form DNAzyme structure that could catalyze the H2O2-mediated oxidation of 2,2′-azino-bis(3-ethylbenzthiazoline)-6-sulfonic acid, generating a dark green color within 5 min which could be observed by naked eye. Notably, the SA demonstrated here showed a wide linear response to PDGF-BB from 0 to 500 nM in bio-samples with a limit of detection as low as 0.7 nM. Therefore, we believe that such an approach should be readily applicable for on-site visual detection of PDGF-BB for cancer monitoring and diagnosis. The newly developed SA strategy also offers attractive universal sensing platforms for rapid and visual detection of other protein biomarkers that only have one binding site.